Because they matter. :O
Originally Posted by Digital_Eon
Why should you care about a purpose? Why do you wish to be remembered in the first place? Do what you want to do. Fulfil your animal desires as well as your intellectual ones.
We also kinda discussed the meaning of life in Ethics.....
The answer is there is no answer....
Some of us are going to do nothing in life,some are trying to become something,some are only going to be average,some are going to change the world....
You just have to find your way - and to at least try to get somewhere in this freaking life.The things that you do matter,even if they or you won´t be remembered in 100 years.Live for yourself,for the moment,for your friends.
Live for pr0n.
Is it just me, or do most people who get philosophical start thinking depressing BS? You don’t need someone to remember you to have a good life. Hell, just graffiti your name somewhere if you’re that worried about it.
The thing is, (I'm not going to read over this whole thread, so if someone already said it, then oh well) that he was remembered. Or else, you woldn't be talking about him.
I'm tired and I misread the title as 'The Fruitility of Life'. That would've been cool. I ate an apple today. It was all good.
Who cares if people don't remember me after I'm dead. I don't know who they are, I'm dead, so why should they know who I am(was)?
Let a = 1, b = 1. a*a = 1, and b*b = 1. From this:
1. a*a - b*b = 0
2. (a + b)*(a - b) = 0
3. (a + b) = 0
Therefore, 1 + 1 = 0, meaning, whatever you add to your life, whatever you do, you'll still end up dead, zero, kaput, nada. This proof, of course, is as cracked up as I am. So don't take my word for it. Go out and find the ever elusive answer to that question.
If I wasn't dead tired I'd find the proof that shows 1=2 and then your whole argument would fall to pieces.
EDIT: I'm not tired enough to get out of this chair and sleep.
Step 1: Let a=b.
Step 2: Then a^2 = ab,
Step 3: a^2 + a^2 = a^2 + ab,
Step 4: 2 a^2 = a^2 + ab,
Step 5: 2 a^2 - 2 ab = a^2 + ab - 2 ab,
Step 6: and 2 a^2 - 2 ab = a^2 - ab.
Step 7: This can be written as 2 (a^2 - a b) = 1 (a^2 - a b),
Step 8: and cancelling the (a^2 - ab) from both sides gives 1=2.